2020
DOI: 10.1111/joa.13302
|View full text |Cite
|
Sign up to set email alerts
|

The claustrum of the sheep and its connections to the visual cortex

Abstract: An important step in understanding the Cl function is to clarify the neurochemistry of the nucleus and identify its reciprocal connections with other brain areas. Efforts are now increasingly drawn toward precising these connections. As an example, here, we mention that there has been no knowledge of direct connection of the Cl to the non-visual thalamus (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…Magnetic resonance imaging has been a widely used diagnostic tool in the study of the central nervous system in sheep. Studies concerning encephalic morphology and tissue volumes with specific interest to the encephalic cortex have been developed and deepened [8][9][10]. Sheep have been mostly studied from a functional point of view, and a cortical map has been created identifying different areas like motor and sensory areas as in humans [11].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging has been a widely used diagnostic tool in the study of the central nervous system in sheep. Studies concerning encephalic morphology and tissue volumes with specific interest to the encephalic cortex have been developed and deepened [8][9][10]. Sheep have been mostly studied from a functional point of view, and a cortical map has been created identifying different areas like motor and sensory areas as in humans [11].…”
Section: Introductionmentioning
confidence: 99%
“…Advances on the knowledge of CLA role in different species have essentially been obtained using immunohistochemical, physiological, and behavioral methods [1,3,[10][11][12][13][20][21][22][23]; a different approach, employing a proteomic analysis, has been used to establish the anatomical definitions of rat CLA [24]. Recently, a single-cell integrating transcriptomic and circuit-level approach, advanced by Erwin et al [25], identified two excitatory CLA neuron subtypes that are molecularly distinguishable from the adjacent cortex.…”
Section: Introductionmentioning
confidence: 99%
“…To conduct fine‐scale functional investigations of brain circuitry, we need accurate anatomical definitions to integrate observations across studies. In many mammals, like primates, cats, dogs, sheep, pigs, dolphins, echidnas, and to some extent rabbits, the CLCX is encapsulated by dense myelinated fibers both medially by the external capsule, and laterally by the extreme capsule (Ashwell et al., 2004 ; Buchanan & Johnson, 2011 ; Cozzi et al., 2014 ; Gattass et al., 2014 ; Kowianski et al., 1999 ; Pham et al., 2019 ; Pirone et al., 2021 , 2015 , 2018 ; Rahman & Baizer, 2007 ; Reynhout & Baizer, 1999 ; Wojcik et al., 2002 ). However, in animals like mice, rats, fruit bats, and pangolins, the extreme capsule is only rudimentary, making it difficult to located claustral borders by white matter alone (Bruguier et al., 2020 ; Imam et al., 2022 ; Kowianski et al., 1999 ; Morello et al., 2022 ; Orman et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%